The Use of Stylistic Means for Shaping Space-Time Perception in The Works of Gabriel Garcia Marquez - Akramjon Nematillayev Gofurjanovich (International Journal Of Literature And Languages, 2025)
This article explores the narrative and stylistic methods Gabriel García Márquez uses to shape the perception of space and time in One Hundred Years of Solitude and Love in the Time of Cholera. It focuses on how lexical choices, narrative structure, temporal looping, symbolic motifs, and magical realism create unique spatiotemporal dimensions within each novel. The study argues that these devices are not ornamental but integral to the novels’ thematic concerns with history, memory, fate, and love. Through close stylistic analysis, the article demonstrates how Márquez builds fictional worlds with their own temporal laws, challenging conventional narrative expectations and enriching literary experience.